ANALISIS PENGENDALIAN KUALITAS PRODUK TELUR AYAM PADA UD AMINA KELURAHAN PETOBO DI KOTA PALU - ANGGRAENI MAHID, DIAH (Fakultas Ekonomi Universitas Tadulako, 2018)
This study aims to determine and analyze the quality control of chicken eggs in an effort to control the level of chicken egg disability and whether the level of disability is within the limits of control at UD Amina Palu. Quality control process applied. UD Amina Palu in chicken egg production is using vasninator service provider of medicines. A common defect criteria for chicken egg production in UD Amina is egg crack criteria as much as 209 eggs, of the four criteria, ie cracking, hollow, thin, pale and broken. The method used is descriptive method with census sampling technique where the samples taken as much as the population produced during 25 working days. This research uses product quality control analysis tool based on Statistical Quality Control (SQC) method for attribute data by using Check Sheet and P-chart disability proportion control chart with standard deviation 3. The result of this research shows that the quality control of defect product done by UD Amina The hammer is in a controlled state or is within the limits of control.